2022
DOI: 10.1038/s41598-022-10051-z
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID occurrence in COVID-19 survivors

Abstract: This cross-sectional study aimed to investigate the post-acute consequences of COVID-19. We conducted a self-administered questionnaire survey on sequelae, psychological distress (K6), impairments in work performance (WFun), and COVID-19–related experiences of stigma and discrimination in two designated COVID-19 hospitals in Hiroshima Prefecture, Japan, between August 2020 and March 2021. The prevalence of sequelae was calculated by age and COVID-19 severity. Factors independently associated with sequelae or p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 35 publications
4
43
1
Order By: Relevance
“…The COVID Symptom Study identified advanced age as a risk factor for long COVID [7]. Approximately one in five COVID survivor of over 70 years of age reported having lasting symptoms [87]. In contrast, self-reporting data from the UK's Office for National Statistic suggested subjects aged from 35 to 69 have the highest prevalence in experiencing long COVID [31].…”
Section: Agementioning
confidence: 99%
“…The COVID Symptom Study identified advanced age as a risk factor for long COVID [7]. Approximately one in five COVID survivor of over 70 years of age reported having lasting symptoms [87]. In contrast, self-reporting data from the UK's Office for National Statistic suggested subjects aged from 35 to 69 have the highest prevalence in experiencing long COVID [31].…”
Section: Agementioning
confidence: 99%
“…Although the introduction of vaccines in January 2021 led to a significant reduction in the number of mild and severe symptomatic patients, the sequelae that COVID-19 can cause in the long term are still cause for concern [ 5 , 6 ]. Sequelae following COVID-19 are various and may include fatigue, muscle and/or joint pain, exercise intolerance, breathlessness, nausea, headaches, memory loss and mood disturbances [ 7 , 8 ]. The WHO uses the term “Post COVID-19 Condition” or “Long Covid” to identify the set of symptomatic sequelae that typically develop within three months of COVID-19 infection, last at least two months, and cannot be explained by alternative diagnoses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The psychological distress was particularly evident among the patients who suffered from COVID (Vahedian-Azimi et al, 2020;Zhang et al, 2020;Imran et al, 2021;Jafri et al, 2022) and were also hospitalized (Guo et al, 2020;Ju et al, 2021;Vlake et al, 2021), despite there being a difference in symptoms and intensity of the disease. The level of distress was more pronounced among people during the initial stages (Cai et al, 2020;Daly and Robinson, 2021), after several months of recovery (Niedzwiedz et al, 2021) and also among women (Sugiyama et al, 2022).…”
Section: Introductionmentioning
confidence: 99%